Development of Electrohydraulic Steering Control System for Tractor Automatic Navigation - Chengqiang Yin; Qun Sun; Jian Wu; Chengqiang Liu; Jie Gao (Journal of Electrical and Computer Engineering)
The most of tractors employed in agriculture are equipped with an electrohydraulic actuator to implement steering control to realize automatic navigation. Electrohydraulic steering system plays an important role in realizing accurate steering control for an automatic navigation tractor because of its complicated characteristics. The objective of this paper is to develop an electrohydraulic steering control system used for automatically guided agricultural tractors. As for the identified electrohydraulic steering system model, a modified Smith control structure was discussed. Based on the structure, an improved design method for voltage servo controller and disturbance rejection controller was proposed to enhance the performance of the steering control subsystem. The effectiveness and the superiority of the proposed method were verified by simulation under Matlab. Simulation results demonstrated the efficiency of the proposed method by showing fast response, control accuracy, and robust performance for the steering control system.